Low dimensional and frustrated antiferromagnetic interactions in transition metal chloride complexes with simple amine ligands. Issue 5 (8th January 2019) - Chalmers, James E.; Srivastava, Anant Kumar; Dixey, Richard J. C.; Sivakumaran, Krrishna; Saines, Paul J.
Abstract : New transition metal chloride complexes with hydrazinium and methylhydroxylamine ligands are reported featuring low dimensional and frustrated magnetic interactions. Abstract : This study reports the facile synthesis, crystal structures and magnetic properties of five new Mn, Co and Cu complexes with chloride and simple amine ligands. The four hydrazinium complexes are discrete in nature while the O -methylhydroxylamine phase contains edge-sharing chains bridged by chloride ligands. Investigation of the magnetic properties of these materials reveals that two of these materials, Co(NH3 NH2 )2 (H2 O)2 Cl4 and Cu(NH2 OCH3 )2 Cl2, exhibit interesting antiferromagnetic properties arising from their low dimensional structures. Co(NH3 NH2 )2 (H2 O)2 Cl4 appears to exhibit significant 2D magnetic frustration while the magnetic susceptibilities of Cu(NH2 OCH3 )2 Cl2 are well fitted by a one-dimensional chain model. The relationships between the strength of the magnetic coupling observed in these materials and their likely exchange pathways are also discussed.